2021
DOI: 10.3390/su132112134
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of Social Media Marketing for Sustainable Business Growth of SMEs in Emerging Economies: The Moderating Role of Leadership Support

Abstract: Social media marketing (SMM) plays an important role in business communication, marketing, operations, and other activities. There is a growing interest among researchers, academicians, and practitioners to understand the role of SMM in business sustainability in small and medium enterprises (SMEs) in an emerging economy, like India. Few studies have attempted to understand this role. Thus, the aim of this study is to examine the impact of adopting social media marketing for sustainable business growth of SMEs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
43
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 77 publications
(96 reference statements)
5
43
0
1
Order By: Relevance
“…Extant studies indicate that there is a relationship between social media usage and sustainable growth of businesses. As such, Chatterjee et al (2021) revealed that social media marketing tools have a significant positive association with sustainable growth of SMEs in India. Similar findings were reported by Patma et al (2021) who documented that social media marketing is positively linked with sustainability of SMEs in Indonesia.…”
Section: Social Media and Mses Growth In Ugandamentioning
confidence: 97%
See 3 more Smart Citations
“…Extant studies indicate that there is a relationship between social media usage and sustainable growth of businesses. As such, Chatterjee et al (2021) revealed that social media marketing tools have a significant positive association with sustainable growth of SMEs in India. Similar findings were reported by Patma et al (2021) who documented that social media marketing is positively linked with sustainability of SMEs in Indonesia.…”
Section: Social Media and Mses Growth In Ugandamentioning
confidence: 97%
“…(see Chatterjee et al, 2021;Scherer et al, 2019) have used TAM to explain technology adoption. The purpose of this model is to predict the readiness and usage of a tool or a certain technology and to identify the modifications which must be brought to the system in order to make it acceptable to users.…”
Section: Social Media and Mses Growth In Ugandamentioning
confidence: 99%
See 2 more Smart Citations
“…First, most studies were from before 2015 and few review articles on hotel marketing have been published during recent years [1][2][3], especially regarding the marketing tools that have undergone tremendous changes. For example, data-oriented marketing [6], digital marketing [7,8], social media marketing [9], online celebrity marketing [10], and sustainable marketing [11,12] have all emerged recently. It is necessary to conduct a comprehensive review of the development trends and marketing tools in hotel marketing in recent years.…”
Section: Introductionmentioning
confidence: 99%